Novel super junction technique used in AlGaN/GaN HEMT for high power applications. (1st July 2022) - Arunraja, A; Jayanthy, S
Abstract: In this paper, a novel super junction technique in AlGaN/GaN HEMT is proposed and analyzed. The novel super junction is capable of splitting the potential drops to two points rather than a single point in the lateral axis (channel axis). Technology Computer Aided Design (TCAD) physical simulator is used to investigate the proposed GaN HEMT. Analyses of the simulation results, shows that the breakdown voltage of proposed AlGaN/GaN HEMT with super junction is higher than that of a conventional device. Proposed device demonstrated a breakdown voltage improvement of 26%. This is due to the reduction of peak electric field using super junction and it is evidenced in the simulation. Further, the Johnson figure of merit (JFOM) is extracted. The JFOM of proposed and conventional AlGaN/GaN HEMT are 4.89 × 1012 V s −1 and 3.79 × 1012 V s −1, respectively. The JFOM in the proposed device is improved by 23%. This improvement is mainly due to the improvement of breakdown voltage rather than cut-off frequency. Overall, the proposed device is a promising candidate for high-power applications as it can withstand higher voltages without compromising the switching-frequency.